Simulations of the 2D self-assembly of tripod-shaped building blocks - Baran, Łukasz; Rżysko, Wojciech; Słyk, Edyta (Beilstein Journal of Nanotechnology, 2020)
We introduce a molecular dynamics (MD) coarse-grained model for the description of tripod building blocks. This model has been used by us already for linear, V-shape, and tetratopic molecules. We wanted to further extend its possibilities to trifunctional molecules to prove its versatility. For the chosen systems we have also compared the MD results with Monte Carlo results on a triangular lattice. We have shown that the constraints present in the latter method can enforce the formation of completely different structures, not reproducible with off-lattice simulations. In addition to that, we have characterized the obtained structures regarding various parameters such as theoretical diffraction pattern and average association number.
Keywords: 2D materials; coarse-grained model; molecular simulations; self-assembly; structural characterization; tripod building blocks